2016
DOI: 10.1080/02678292.2016.1189613
|View full text |Cite
|
Sign up to set email alerts
|

Dyes as guests in ordered systems: current understanding and future directions

Abstract: The optical properties of dyes dissolved in liquid crystals have led to their proposed use in a diverse range of practical applications. Such guest-host systems are typically required to fulfil a range of criteria relating to their absorption properties, degree of alignment and stability, but concurrently satisfying these requirements has proven a barrier to their widespread use. In this article, many of the proposed applications and their requirements are discussed, and an outline of some of the most prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 103 publications
1
23
0
Order By: Relevance
“…The alignment of dyes in guest-host systems is generally quantified by a dichroic order parameter in which the orientation of the TDM is considered to be fixed within the molecular frame of the dye, as discussed in the Introduction and as given by eqn (2). This assumption may be valid for many dyes, and particularly for those with rigid chromophores, but its validity may need to be assessed for more flexible systems.…”
Section: Influence Of Flexibility On Tdm Orientationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alignment of dyes in guest-host systems is generally quantified by a dichroic order parameter in which the orientation of the TDM is considered to be fixed within the molecular frame of the dye, as discussed in the Introduction and as given by eqn (2). This assumption may be valid for many dyes, and particularly for those with rigid chromophores, but its validity may need to be assessed for more flexible systems.…”
Section: Influence Of Flexibility On Tdm Orientationsmentioning
confidence: 99%
“…Dyes are often used as the guest molecules in such systems to provide optically anisotropic mixtures, for which a wide variety of applications have been proposed. 1,2 Most prominently, guest-host systems have been investigated for applications in display devices that can provide higher optical and energy efficiency than conventional LCD devices, along with the ability to operate in light-scattering modes in sheltered environments or outdoors. 3 In addition, guest-host systems have been suggested for a diverse range of other applications that include precursors for high performance thin-film polarizers, 4 optical storage devices utilising photochemical dye isomerisation, 5 optically controlled diffraction gratings, 6 security devices, 7 switchable windows using fluorescent guest molecules to collect solar energy, 8 and 3D imaging of micellar systems also using fluorescent dyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on LC devices with guest–host systems have showed enhanced optical and switching properties. [ 23,24 ] Adaptive windows that can adjust the light transmission according to the climatic conditions (allow more solar heat to enter in winter and less in summer) are in high demand. [ 25 ] Studies have proven that the guest–host LC devices are the most eligible candidates for such adaptive windows.…”
Section: Introductionmentioning
confidence: 99%
“…The dichroic order parameter is related directly to the absorbances, A || and A ⊥ , according to Equations (2) and (3), respectively [16], where ε is the absorption coefficient of the visible absorption band of the dye, c is the concentration of the dye and l is the path length of the cell.…”
Section: Introductionmentioning
confidence: 99%